Tensions in teacher preparation accountability, assessment, and accreditation - Erickson, Lynnette B.; Wentworth, Nancy (Bingley, U.K. : Emerald, 2010)
Current accreditation practices require that teacher education institutions in the United States not only create programs that enact research-based best practices but that they also document their existence and efficacy in preparing teachers.'Tensions in Teacher Preparation: Accountability, Assessment, and Accreditatio' addresses the challenges of meeting national accreditation requirements, including designing assessment instruments and making data-driven decisions. The process of establishing and implementing accountability creates tensions in faculty and institutions. Faculty must give up valued content and instructional styles in order to align course objectives and assessment instruments across the program. Institutions with multiple licensure programs must make adjustments in order to share data collection instruments and processes that will support data-driven decisions. The paradigm shifts required by the emphasis on accountability can be both frustrating and productive. This book explores and shares tensions created as teacher education programs experience changes because of accountability requirements related to the accreditation process.
ch. 1. Tensions : negotiating the challenges of accountability and accreditation / Nancy Wentworth, Lynnette B. Erickson -- ch. 2. Educating the educators : accreditation as a teaching and learning tool / Ann Monroe-Baillargeon -- ch. 3. Decorating for NCATE / Richard D. Osguthorpe, Jennifer L. Snow-Gerono -- ch. 4. Tensions, collaboration, and pizza create paradigm shifts in a teacher education program / Lynnette B. Erickson, Nancy Wentworth, Sharon Black -- ch. 5. International perspectives on accountability and accreditation : are we asking the right questions? / Brenda L.H. Marina, Cindi Chance, Judi Repman -- ch. 6. Living with accreditation : realizations and frustrations of one small university / Judith A. Neufeld -- ch. 7. Is this data useful? : the impact of accreditation on the development of assessments / Sam Hausfather, Nancy Williams -- ch. 8. Making stone soup : tensions of national accreditation for an urban teacher education program / Carolyne J. White, Joelle J. Tutela, James M. Lipuma, Jessica Vassallo -- ch. 9. Developing data systems for continuous improvement under the NCATE structure : a case study / Elaine Ackerman, John H. Hoover -- ch. 10. What's that noise? : things that keep us awake at night : the cost of unexamined assumptions in pre-service assessment and accreditation / James H. Powell, Letitia H. Fickel, Patricia Chesbro, Nancy Boxler -- ch. 11. Revisiting self in the midst of NCATE and other accountability demands / Cheryl J. Craig -- ch. 12. Does national accreditation foster teacher professionalism? / Ken Jones, Catherine Fallona -- ch. 13. Soothing Cerberus : the Wyoming odyssey / Linda Hutchinson, Alan Buss, Judith Ellsworth, Kay Persichitte -- ch. 14. Accreditation : responding to a culture of program evaluation / Linda E. Pierce and Susan Simmerman -- ch. 15. Western governors university : a radical model for preservice teacher education / Thomas W. Zane, Janet W. Schnitz, Michael H. Abel -- ch. 16. Transformation from tension to triumph : three perspectives on the NCATE process / James M. Shiveley, Teresa McGowan, Ellen Hill -- ch. 17. Reflections on the shared ordeal of accreditation across institutional narratives / Lynnette B. Erickson, Nancy Wentworth.
Keywords: Teachers -- Training of